Severe volcanic SO2 exposure and respiratory morbidity in the Icelandic population - a register study - Hanne Krage Carlsen; Unnur Valdimarsdóttir; Haraldur Briem; Francesca Dominici; Ragnhildur Gudrun Finnbjornsdottir; Thorsteinn Jóhannsson; Thor Aspelund; Thorarinn Gislason; Thorolfur Gudnason (BMC, 2021)
Abstract Background The Holuhraun volcanic eruption September 2014 to February 2015 emitted large amounts of sulfur dioxide (SO2). The aim of this study was to determine the association between volcanic SO2 gases on general population respiratory health some 250 km from the eruption site, in the Icelandic capital area. Methods Respiratory health outcomes were: asthma medication dispensing (AMD) from the Icelandic Medicines Register, medical doctor consultations in primary care (PCMD) and hospital emergency department visits (HED) in Reykjavík (population: 215000) for respiratory disease from 1 January 2010 to 31 December 2014. The associations between daily counts of health events and daily mean SO2 concentration and high SO2 levels (24-h mean SO2 > 125 μg/m3) were analysed using generalized additive models. Results After the eruption began, AMD was higher than before (129.4 vs. 158.4 individuals per day, p < 0.05). For PCMD and HED, there were no significant differences between the number of daily events before and after the eruption (142.2 vs 144.8 and 18.3 vs 17.5, respectively). In regression analysis adjusted for other pollutants, SO2 was associated with estimated increases in AMD by 0.99% (95% CI 0.39-1.58%) per 10 μg/m3 at lag 0-2, in PCMD for respiratory causes 1.26% (95% CI 0.72-1.80%) per 10 μg/m3 SO2 at lag 0-2, and in HED by 1.02% (95% CI 0.02-2.03%) per 10 μg/m3 SO2 at lag 0-2. For days over the health limit, the estimated increases were 10.9% (95% CI 2.1-19.6%), 17.2% (95% CI 10.0-24.4%) for AMD and PCMD. Dispensing of short-acting medication increased significantly by 1.09% (95% CI 0.49-1.70%), and PCMD for respiratory infections and asthma and COPD diagnoses and increased significantly by 1.12% (95% CI 0.54-1.71%) and 2.08% (1.13-3.04%). Conclusion High levels of volcanic SO2 are associated with increases in dispensing of AMD, and health care utilization in primary and tertiary care. Individuals with prevalent respiratory disease may be particularly susceptible.